Combinatorial double auction-based allocation of retrieval tasks in Internet of Things - Zhi-kai XU; Hong-li ZHANG; Xiang-zhan YU; Zhi-gang ZHOU (Tongxin xuebao)
Task allocation mechanism was greatly important to the success of the search service in Internet of Things (IoT).On basis of analyzing the real time characteristics of the IoT data,and the dynamic characteristics of the users,a combinatorial double auction-based retrieval tasks allocation model was introduced,which described the relationships between the workers,the requesters and the system from the perspective of supply and demand.Firstly,a novel metric to evaluate the value of the users’ queries was introduced and a greedy heuristic algorithm to determine the winning requesters and workers was proposed.Then,a critical payment scheme was proposed,which guaranteed that submitted bids of the users reflect their real value.Finally,both the rigid theoretical analysis and simulation result show that the proposed mechanism achieves truthfulness,individual rationality and the efficiency of the service provider is improved.